Offending Histories and Typologies of Suspected Sexual Offenders Identified Via Untested Sexual Assault Kits - Lovell, Rachel (Criminal justice and behavior, 2020)
In this study, we present findings that detail the criminal offending histories and typologies of suspected sexual offenders identified from an initiative to follow up on the testing of thousands of previously untested sexual assault kits (SAKs). This study advances our understanding of sexual offenders by incorporating data from criminal justice system records (“detected” criminal offending) with data from newly tested SAKs that were not previously adjudicated (“undetected” sexual offending). Our findings demonstrate that these offenders have extensive criminal histories, very frequently continued to offend after the SAK-associated sexual assault, and, more often than not, have criminal histories that do not include a prior arrest(s) for rape. A latent class analysis identified three classes of offenders based on their offending history, “High-Volume Generalists,” “Low-Volume Offenders,” and “Sexual Specialists.” Most were generalists, with a large proportion committing lots of serious crimes.